THE EXISTENCE OF MUSLIM-FRIENDLY KOS TREND IN MALANG CITY: DO THE PEOPLE OF MALANG REJECT INTOLERANCE?: CASE STUDY IN MERJOSARI VILLAGE, MALANG CITY - Holikul Mubin (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study examines the phenomenon of the existence of Muslim/Muslimah-exclusive boarding houses in Merjosari Village, Malang City. The research aims to explore and understand the underlying reasons for the presence of the